Finding, characterizing and classifying variable sources in multi-epoch sky surveys: QSOs and RR Lyrae in PS1 3π data - Hernitschek, Nina; Grebel, Eva K. (Arxiv, 2015)
In area and depth, the Pan-STARRS1 (PS1) 3$π$ survey is unique among many-epoch, multi-band surveys and has enormous potential for all-sky identification of variable sources. PS1 has observed the sky typically seven times in each of its five bands (